The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1088/1361-6528/ab2ca6
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the localized surface plasmon resonance of Ag@SiO2 core-shell nanocubes and its application in high-performance blue organic light-emitting diodes

Abstract: A blue organic light-emitting diode (OLED) with silica-coated silver nanocubes (Ag@SiO 2 NCs) inserted at the hole transporting layer/emission layer interface is reported. The localized surface plasmon resonance (LSPR) properties of the Ag@SiO 2 NCs were characterized by the measured absorption spectra, stable-stated and transient photoluminescence, and calculated dipole radiation power. The results suggest that the Ag NCs significantly improved the radiation intensity of the nearby excitons due to their sharp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…At the LSPR wavelength, the AgNPs exhibit near-field enhancement of electromagnetic fields that improves the light output-coupling. [39][40][41] In addition to the function of enhancing light extraction, MoO x in the LOCL can effectively isolate water and oxygen to achieve a good packaging effect.…”
Section: Characterizations Of the Teoledsmentioning
confidence: 99%
“…At the LSPR wavelength, the AgNPs exhibit near-field enhancement of electromagnetic fields that improves the light output-coupling. [39][40][41] In addition to the function of enhancing light extraction, MoO x in the LOCL can effectively isolate water and oxygen to achieve a good packaging effect.…”
Section: Characterizations Of the Teoledsmentioning
confidence: 99%
“…The past decade has witnessed a significant rise in LSPR enhancement of visible OLEDs with noble metal (Au or Ag) nanostructures resulting in 20–60% improvement in efficiency ( Deng et al., 2019 ; Wu et al., 2018 ; Munkhbat et al., 2016 ). Noble metal nanostructures are promising thanks to their unique physical and chemical properties, efficient dispersibility in solvents for solution processing, and moderate costs of production.…”
Section: Approaches To Nir Light Generationmentioning
confidence: 99%
“…Huang et al reported that silver nanoparticles were doped to enhance the luminescence . These enhancements may be attributed to the surface plasmon resonance (SPR) effect as the NPs interact with the incident light. , However, owing to their intrinsically narrow SPR bands peaking at around 520 nm, none have yet reported any significant improvement for devices in the red or near-infrared red (NIR) region, even with the employment of their mixtures, alloys, or surface modified counterparts. , …”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28][29][30]46 However, owing to their intrinsically narrow SPR bands peaking at around 520 nm, 33 none have yet reported any significant improvement for devices in the red or near-infrared red (NIR) region, even with the employment of their mixtures, 34−36 alloys, 37 or surface modified counterparts. 43,45 Nanocopper particles possesses unique properties that make them useful in a wide range of applications. Due to their small size and high surface area, they exhibit high reactivity and efficiency in catalytic and electrochemical reactions.…”
Section: ■ Introductionmentioning
confidence: 99%